Achieving leadership behavior change at scale. Issue 6 (1st November 2018) - Rose, Tom
Abstract : Purpose: The growing force of disruptive change is creating whitewater work environments across the profit and not-for-profit world. To help leaders overcome the challenge of achieving improvements in leadership performance, this study aims to outline research and case examples that illustrate a four-point roadmap for improving this performance at scale. Design/methodology/approach: The study summarizes new research on leadership and organizational high performance and practices that drive high performance today. It relates these finding to trends evidenced in the work being done by HR organizations and the consulting firms that serve them. It then outlines an evidence-based roadmap for achieving improvements in leadership performance that HR organizations can adopt to achieve improvements in leadership performance. Findings: Successful organizations intervene at four leverage points to meet the challenge achieving the shifts in leadership behavior needed for success in today's permanent whitewater environments. These organizations are focusing on two types of leadership, leveraging two approaches to its development and are leveraging critical enablers that benefit from strong alignments within HR and between HR and their business leader colleagues. Originality/value: The study highlights new research finding and research-based models of leadership performance that meet the demands of today's workplace. It synthesizes a new four-point roadmap to success from trends discovered in recent research on leadership, technology-assisted behavior change and organizational effectiveness, as well as in the example of in high-performing organizations.